Potential of The Biological Agent Bacillus spp in Inhibiting Fusarium Wild Disease and its Effects on The Growth and Production of Cayenne Papper (Capsicum frutescens L.) - Zakqy, Nauval; Wuryandari, Yenny; Purnawati, Arika (Universitas Labuhanbatu, 2024)
Cayenne pepper (Capsicum frutescens L.) is a horticultural crop in Indonesia that often has many obstacles. The main obstacle that is often faced is wilt disease caused by the fungus Fusarium oxysporum. Bacillus spp. bacteria have the potential to control the fungus F. oxysporum. The purpose of this study was to determine the ability of Bacillus spp. bacteria in controlling fusarium wilt disease. This research was conducted from August to November 2023 at the Plant Health Laboratory and screen house of the Faculty of Agriculture, National Development University